Wage bargaining and political strength in the public sector - Torberg Falch; Bjarne Str?m (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper analysis the link between political strength and public sector wages using a unique matched individual-employer data set for Norwegian local governments during the period 1990-1998. The results indicate that political strength, measured in several ways, has a positive effect on wages, while administrative strength, measured by the tenure of the chief executive, has a negative effect. The positive effect of political strength is consistent with a model in which the budgetary process is a multistage game and employment is determined in an interaction with interest groups prior to the wage bargain.
Keywords: H72; D73; J45; 330; public sector labor market; wage bargaining; political strength; budgetary process; Besoldung; Lohnverhandlungstheorie; Public Choice; Macht; Kommunalverwaltung; Schätzung; Norwegen